Cyber-Senga: Ugandan youth preferences for content in an internet-delivered comprehensive sexuality education programme - Bull, Sheana; Nabembezi, Dennis; Birungi, Ruth; Kiwanuka, Julius; Ybarra, Michele (East African journal of public health, 2010)
Globally more than 37 million people have been infected with the HIV virus. [1] Sub-Saharan Africa remains the region most heavily affected by HIV, accounting for 67% of all young people living with HIV and for 75% of AIDS deaths in 2007. [2] In Uganda, adolescents are at increased risk of HIV infection compared to any other age group. [3] Evidence from the AIDS Information Centre shows that among 15–24-year-olds who were testing for the first time, HIV prevalence was 3% among young men and 10% among young women in 2002. Since 2000, Uganda’s HIV prevalence rates have been characterized by stabilization at a level ranging from 6–7% [2] There are indications from the national surveillance system corroborated by data from longitudinal cohort studies however, of an apparent increase in HIV prevalence and incidence during the last few years. [2] Thus, not only are young people are still vulnerable to HIV infection in Uganda, but that risk may be increasing.
Keywords: Internet; HIV prevention; Uganda; Adolescent health